2013
DOI: 10.1155/2013/603683
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Infiltrating Ductal Carcinoma of the Breast to the Colon: A Case Report and Literature Review

Abstract: True metastatic involvement of the colon is rare. Colonic metastases occur most commonly secondary to peritoneal metastases from intra-abdominal malignancies. Breast cancer is the most common malignancy that metastasizes hematogenously to the colon. Colonic metastatic disease mimics primary colonic tumors in its presentation. Colonic metastatic involvement is a poor prognostic sign, and the pathologist should be informed about the history of the primary breast cancer when examining the pathologic specimens. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Based on the review of the literature, presentation of metastatic disease to the colon can be variable [ 1 - 3 , 5 ]. It can be asymptomatic or it can present with signs of intestinal obstruction, such as nausea, vomiting, and abdominal distension [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the review of the literature, presentation of metastatic disease to the colon can be variable [ 1 - 3 , 5 ]. It can be asymptomatic or it can present with signs of intestinal obstruction, such as nausea, vomiting, and abdominal distension [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…GI metastasis from breast cancer is rare [1][2][3][4][5][6][7][8]. Several case reports have examined the incidence and significance of this finding.…”
Section: Discussionmentioning
confidence: 99%
“…A few case reports have also demonstrated the rarity of metastasis of invasive ductal carcinoma to the colon. Although invasive ductal carcinoma is more common than invasive lobular carcinoma, the latter metastasize more frequently to the GI tract and retroperitoneum [2,[4][5][6][7][8]. Eljabu et al reported that invasive lobular carcinoma accounts for 64% of GI metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations